When “the place” is the classroom - Verdasco Novalvos, Ángel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
In architecture, “the place” has frequently been a project motif and has thus been explained as such. In this study, however, the place is considered under new light, in a different facet, which is as relevant as any other: its pedagogic side, the teaching of architecture and how the classroom gives birth to projects, many of which may have an educational purpose. The classroom is often the first place where architecture is produced. For this reason, many architects have been interested in participating in the debate on how architecture should be taught, if, as some think, this is at all possible. In this article we follow the work of Curro Inza, architect and teacher who understood the classroom as the initiating place of the project, and he created a new and revolutionary teaching method with consequences and impact which can be noted today. In this study, we show some of Curro Inza’s unpublished material consisting of educational projects and we also explain his unique pedagogic methodology. Curro Inza developed his teaching career at the Universidad de Pamplona, a young and promising institution at his time. Therefore what we present in this article may have a speculative character.